Problems of developing a strategic planning methodology for regional socio-economic systems - A. G. Ataeva (Управление)
The issues of the methodology for developing regional strategies have been considered in three aspects: firstly, from the position of restrictions on the use of traditional strategic planning schools in relation to the regional socio-economic systems; secondly, in the context of the characteristics of the region as an object of strategic planning; thirdly, taking into account modern realities of information technology development and management decision-making tools. It has been it has been revealed, that traditional strategic management schools take into account only a certain aspect of strategizing and have limited application for regional systems. The peculiarities of the region have been have been disclosed as an open complex system, occupying an intermediate level in the public administration system, characterized by a non-linear development and informational openness of management.The complex nature of a region affects the fact, that a regional strategy is a mechanism for coordinating the long-term interests of various stakeholders of a territory. This happens both through their participation in determining strategic priorities and selecting specific strategic projects at the goal setting stage, and through the use of special model tools, which are characterized by the presence of built-in interaction loops for different classes of economic situations and allowing them to adapt their resource strategies while agreeing on common goals of functioning. It has been ascertained, that the current stage of economic development is characterized by features related to the development of information technologies and management decision-making tools, which determines the need to expand the methodological and methodical base of the regional strategic planning.In total, the analysis shows, that in the context of the adaptive behavior of economic agents of the region, the uncertain external and internal environment, traditional methodological approaches and methodical tools become of little use in the actual practice of regional governance. The effective direction of improving the methods of strategic planning in these conditions is the use of adaptive management and simulation modeling technologies based on modern information technologies.